TESTING AND IMPLEMENTATION OF FORWARDING STRATEGY IN MINI-NDN-BASED NAMED DATA NETWORKING TESTBED - Mulya Harjono, Hafizh
Named Data Networking is a promising candidate for future internet architecture, but its forwarding strategy has not been thoroughly explored. Exploration of NDN